Strengthen markets to aid farmers: The NDA government's aim of doubling farmers’ income continues to remain a distant dream - Kishore, Avinash (HT Media Ltd, 2018)
The National Democratic Alliance (NDA) government’s renaming of ministry of agriculture as the ministry of agriculture and farmers’ welfare, and the promise to double farmers’ income by 2022, signals a clear shift in India’s agricultural policy.